2020
DOI: 10.7203/sjp.28.2.17853
|View full text |Cite
|
Sign up to set email alerts
|

A database of Triassic conodonts from a comprehensive revision of literature

Abstract: The revision of a comprehensive amount of bibliography has made possible the development of a database containing the stratigraphic ranges of the conodont species from the uppermost Permian and the Triassic, with a total of 336 species in 52 genera. This database is aimed at biostratigraphy and studies related to biological, evolutional and palaeodiversity dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The conodont database in Plasencia et al (2013) includes most Carnian conodont species from western Tethys and North American. Data from the database indicate a conodont diversity decrease from 25 species in Julian 1 to 9 species in Julian 2.…”
Section: Discussionmentioning
confidence: 99%
“…The conodont database in Plasencia et al (2013) includes most Carnian conodont species from western Tethys and North American. Data from the database indicate a conodont diversity decrease from 25 species in Julian 1 to 9 species in Julian 2.…”
Section: Discussionmentioning
confidence: 99%
“…The generic assignement of the species gondolelloides has also been interpreted either as Spathognathodus (Bender, 1970), Neospathodus (Sweet, 1970a(Sweet, , 1973Orchard, 1995), Gondolella (Kozur, 1973b;Gaetani et al, 1992), Kashmirella (Budurov et al, 1988b(Budurov et al, , 1989Budurov & Sudar, 1995;Kiliç et al, 2016) or Chiosella (Kozur, 1989b;Orchard & Bucher, 1992). More recently, the assignement of the species gondolelloides was limited to Chiosella (e.g., Klets, 2008;Orchard, 2010;Plasencia et al, 2013;Muto et al, 2019). Furthermore, Nicora (1977), Kozur (1989b) and Gaetani et al (1992) treated Neogondolella aegaea Bender, 1970 as a junior synonym of Chiosella timorensis, thus implying the equivalence between the Timorensis Zone of Sweet (1970a), placed in the top of the Spathian, with "Die aegaea -Zone" of Bender (1970b), placed in the Anisian.…”
Section: Chiosella Timorensis a Conodont Having A Highly Controversial Taxonomy And Definitionmentioning
confidence: 99%
“…This gives rise to uncertainties with regard to many of the older reported occurrences of the true conodont species timorensis. Plasencia et al (2013), based on a comprehensive revision of the Triassic conodont literature, found that the stratigraphic range of Ch. timorensis is from the late Spathian to the early Pelsonian.…”
Section: Chiosella Timorensis a Conodont Having A Longdisputed First Occurrence And Chronostratigraphic Rangementioning
confidence: 99%